P-009 Endovascular balloon-augmented embolization of intracranial and cervical arteriovenous malformations using a dual lumen coaxial balloon microcatheter: initial experience. (4th July 2012) - Grigoryan, M; Hassan, A; Tummala, R; Tekle, W; Seidel, G; Jagadeesan, B
Abstract : Background: Transarterial embolization with ethylene vinyl alcohol copolymer (EVOH) Onyx (ev3, Neurovascular, Irvine, CA) is a popular method for endovascular management of arteriovenous malformations (AVMs) and fistulas. Successful embolization depends on antegrade flow of Onyx following initial formation of a proximal plug. Plug formation can be unpredictable, time consuming and can result in catheter retention. To avoid the need for forming a proximal plug, we recently adopted Onyx embolization through a coaxial balloon microcatheter. Methods: We performed a series of five consecutive Onyx embolizations via seven arterial feeders in four patients using the Scepter C (Microvention Inc, Tustin, CA), a coaxial balloon catheter with an inner lumen for a guidewire and an outer lumen for balloon inflation/deflation. In each case, the catheter was navigated into the feeding artery over an 0.014 wire. After removing the wire, the balloon was then carefully inflated to arrest the flow and prevent reflux of Onyx. The inner lumen was primed dimethyl sulfoxide and Onyx 18 or 34 was then infused under continuous fluoroscopic visualization. Embolizations were terminated following adequate penetration of the AVM nidus. The balloon was then deflated and catheter was slowly removed without difficulties. Results: The balloon catheter showed excellent navigability and there were no complications involving its inflation, deflation, or retrieval. There was no reflux of Onyx. Excellent penetration into the AVM nidus was achieved during all sessions. No untoward embolization into the normal cerebral circulation has occurred. None of the patients suffered peri- or postprocedural complications. Conclusions: Onyx embolization via a coaxial lumen Scepter C balloon catheter allows for great penetration while obviating the need for the usual "plug and push technique". It reduces procedure time and radiation exposure. Due to its current availability in only one size (4 mm), the technique may be safest in larger diameter arterial feeders. Competing interests: None.